Aphrodisiac potential of Polyalthia bullata (Tongkat Ali) in fowl - Jaya Vejayan, Palliah; Yasmin Amira, Che Yahya; Chakravarthi, Srikumar; Halijah, Ibrahim; Aida, Yun (Wolters Kluwer Medknow Publications, 2021)
Objective: To study the aphrodisiac potential of Polyalthia (P.) bullata in fowl. Methods: In this study, testosterone, as an indicator of the aphrodisiac potential of P. bullata, was investigated for its release from TM3 Leydig cells grown in vitro and in 4 fowls given capsules containing P. bullata at a dose of 10 mg in each capsule twice a day, for 50 days. In the latter in vivo evaluation, mating behaviours were additionally determined after the treated fowls were released to the individual hens, and their testes and liver were dissected for histological examinations. Blood drawn from the fowls was assessed for any changes in diagnostic parameters. Results: In the in vitro test (TM3 Leydig cells), P. bullata was able to increase testosterone to 0.48 nmol/L within 72 h of incubation, compared to the untreated control with only 0.18 nmol/L, i.e., an increase of 170%. In the in vivo test, outcomes in the fowls dosed with P. bullata showed similar positive elevations of testosterone to (9.72±1.10) nmol/L in comparison to the controls that showed a level of only (4.05±0.84) nmol/L. Total frequencies of mating behaviours were observed (wing flapping, body shakes, crowing and beak pecking) to be 23 counts for the test compared to only 15 for the control fowls. Histological examination of the male reproductive organs provided evidence of testosterone boosting based on an observable increase in the activity at the seminiferous tubules of testis tissues without any damaging effects, compared to the controls. In the nine diagnostic blood parameters assessed, including alanine aminotransferase, aspartate aminotransferase, and gamma glutamyltransferase, none was remarkably elevated compared to the controls. The histological changes in the liver were not severe and mainly consisted of only localized moderate but recoverable obstructions and swellings of the vessels and tubules. Conclusions: P. bullata is able to boost testosterone both in vitro and in vivo, with no acute toxicities.